Estudo paleoetnobotânico do Crastro de Palheiros na Idade do Ferro: uma análise carpológica - Leite, Margarida Isabel (2017)
Through carpological analysis of the Dwelling Area 6 of Crasto de Palheiros, we aim to contribute to the understanding of the chrono-spatial and functional organization of the Enclosure L at Lower Eastern Platform, in an attempt to expand the knowledge of storage, processing and consumption strategies, based on taxonomic identification and comparison to previous results. In small quantities there is a presence of cereals hulled wheats (Triticum dicoccum and Triticum spelta), barley (Hordeum) and fruits of Arbutus unedo. There are also grapes (Vitis vinifera).